2019
DOI: 10.1177/0092055x19860563
|View full text |Cite
|
Sign up to set email alerts
|

Do Sociology Courses Make More Empathetic Students? A Mixed-Methods Study of Empathy Change in Undergraduates

Abstract: Assessing course goals is often challenging; assessing an abstract goal, like empathy, can be especially so. For many instructors, empathy is central to sociological thinking. As such, fostering empathy in students is a common course goal. In this article, we report the initial findings of a semester-long assessment of empathy change in undergraduate students ( N = 619). We employ a mixed-methods research design that utilizes qualitative instructor data to determine independent instructor-level variables and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Sociologists have dedicated increasing attention toward teaching students how to become more empathetic toward the hardships of others (Ghidina 2019; Latshaw 2015; MacNamara, Glann, and Durlak 2017; Rockwell et al 2019; Romero 2020), but what practices are we incorporating into our pedagogy to demonstrate our own compassion toward students, especially during a pandemic or other social disruptions? What does it mean to be a compassionate teacher?…”
Section: Lessons In Compassion and Accessibilitymentioning
confidence: 99%
“…Sociologists have dedicated increasing attention toward teaching students how to become more empathetic toward the hardships of others (Ghidina 2019; Latshaw 2015; MacNamara, Glann, and Durlak 2017; Rockwell et al 2019; Romero 2020), but what practices are we incorporating into our pedagogy to demonstrate our own compassion toward students, especially during a pandemic or other social disruptions? What does it mean to be a compassionate teacher?…”
Section: Lessons In Compassion and Accessibilitymentioning
confidence: 99%
“…In doing so, students developed empathy for victims of microaggressions. This sense of empathy, which mirrors the empathy development that students experience in sociology courses more generally (Rockwell et al 2019), led many students to commit to personal change. For students, this meant vowing to commit fewer microaggressions and being more responsive when told about microaggressions they have committed.…”
Section: Resultsmentioning
confidence: 80%
“…Fifth, and most pressingly, we cannot know whether or not students who decide to major in a humanities or social sciences discipline are more empathic to begin with, and therefore it is possible we are measuring more empathic students who gravitate toward humanities and social sciences rather than real differences in the impacts of these disciplines. While we cannot measure the impact directly, in work measuring empathy of sociology students, Rockwell et al (2019: 293) found no evidence that students choosing to enroll in sociology classes had higher levels of empathy than others.…”
Section: Discussionmentioning
confidence: 89%